The Relationship Between Mother's Knowledge And Nutritional Status With Toddlers' Growth In The Working Area Of Jagong Puskesmas Central Aceh District, 2020 - Juliana Munthe (Institute of Computer Science (IOCS), 2021)
Based on the results of Riskesdas (2018), it can be seen that from 82,661 toddlers who were weighed nationally, there was a prevalence of underweight as much as 19.6%. The working area of the Jagong Health Center, Central Aceh Regency, was used as the research location, referring to the data at the Puskesmas and it was recorded that 87 toddlers (35.7%) had nutritional status below the red line. This type of research is observational with a cross sectional approach. The population in this study were all toddlers in the Jagong Health Center Work Area, Central Aceh Regency in 2021, which were 284 people. Samples were taken by simple random sampling method as many as 48 people, analysis technique using chi square. The proportion of toddlers whose growth and development is not normal is 30 people (62.5%) more than toddlers whose growth and development is normal, which is 18 people (37.5%). There is a significant relationship between mother's knowledge and nutritional. It is recommended to health workers at the Jagong Health Center to hold an outreach program for mothers who have toddlers about the importance of efforts to improve nutrition for families, especially toddlers.